Evaluasi Jaringan Irigasi Saluran Sekunder pada Daerah Irigasi Kerasaan Kabupaten Simalungun - Purba, Musa Affandy; Wulandari, Tika Ermita (Portal: Jurnal Teknik Sipil, 2025)
The Kerasaan Irrigation Area is an irrigation area located in Simalungun Regency, North Sumatra Province. With a functional area of 5000 (Ha) and a secondary irrigation channel area of 39.10 (km). In optimizing irrigation performance in the DI Kerasaan irrigation area, irrigation network infrastructure maintenance must be carried out, one of which is by evaluating the irrigation channels in the area. This evaluation aims to determine and analyze the condition and function of irrigation assets in the Kerasaan irrigation area, so that the function of the irrigation channels can be optimized to irrigate the lands in the irrigation area. The method used in evaluating the irrigation channel is the observation method by tracing the irrigation network using a GPS device to determine the coordinates of the channel points and documenting asset damage with a camera/mobile phone. Based on the results of the analysis, the total length of damage to the paired channel structure was 10 m from a combination of several segments in 2 channel sections in the secondary channel with a total damage index of 0.70%. In the secondary Kerasaan channel from the survey results as far as (±1000 m) in the field there are 2 units of buildings for tapping and 3 units for tapping. The results of the analysis can be used for planning the construction of irrigation structures by planning structural buildings, water gates and measuring buildings.